Upaya Masyarakat dan Pemerintah Desa dalam Melestarikan Tradisi Pantauan Bunting di Desa Lebak Budi Kecamatan Merapi Barat Kabupaten Lahat - Puspita Sari Sari; Hudaidah Hudaidah (Jurnal Ragam Pengabdian, 2026)
The Bunting Observation Tradition is one of the intangible cultural heritages that is still sustainable in Lebak Budi Village, West Merapi District, Lahat Regency. The tradition plays a significant social role, especially in the context of the wedding ceremony as a form of respect, a symbol of sanctity, and strengthening kinship. However, the wave of modernization and social transformation has caused various challenges to the continuation of this tradition. This study aims to outline the efforts made by the community and the village government to maintain the tradition of preserving the Bunting Monitoring tradition. This study applies a qualitative approach with a type of descriptive research that includes data collection methods through observation, interview, and documentation. This research shows that the community is also active in preservation through cultural transfer, contributions of traditional figures, gotong royong activities, and innovative adaptations. Meanwhile, the village government provides support through local regulations, educational programs, and traditional documentation. The cooperation between the two parties has proven to be effective in maintaining the sustainability of tradition until now. This study emphasizes that the synergy between the community and the village government is an important part of cultural development.